Adolescent Physiological and Behavioral Patterns of Emotion Dysregulation Predict Multisystemic Therapy Response. (September 2017) - Winiarski, D. Anne; Schechter, Julia C.; Brennan, Patricia A.; Foster, Sharon L.; Cunningham, Phillippe B.; Whitmore, Elizabeth A.
This study examined whether physiological and behavioral indicators of emotion dysregulation assessed over the course of multisystemic therapy (MST) were related to treatment response. Participants were 180 ethnically diverse adolescents ( n = 120 males), ranging in age from 12 to 17 years. Treatment response was assessed through therapist report and official arrest records. Changes in cortisol reactivity and changes in scores on a Behavioral Dysregulation subscale of the Child Behavior Checklist were used as indicators of emotion dysregulation. Hierarchical linear modeling analyses examined whether a less favorable treatment response was associated with cortisol reactivity measures collected (a) early in treatment and (b) over the course of treatment as well as with behavioral reports of emotion dysregulation reported (c) early in treatment and (d) over the course of treatment. Sex was explored as a moderator of these associations. Results indicated that both cortisol and behavioral indices of emotion dysregulation early in treatment and over the course of therapy predicted treatment responsiveness. This relationship was moderated by sex: Girls were more likely to evidence a pattern of increasing emotion regulation prior to successful therapy response. The results lend further support to the notion of incorporating emotion regulation techniques into treatment protocols for delinquent behavior.